Digital Transformation and Innovation : Driving Business Growth - Surendra Mohan Devaraj (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article explores the symbiotic relationship between digital transformation and innovation in driving business growth. It examines the key components of digital transformation, including cloud computing, big data analytics, AI, IoT, cybersecurity, and digital platforms. The article discusses how digital transformation catalyzes innovation through data-driven decision-making, fostering experimentation, enhancing collaboration, and accelerating time-to-market. It outlines the competitive advantages of digital transformation, such as improved customer experience, operational efficiency, new revenue streams, agility, and talent attraction. Case studies of successful digital transformations are presented, along with an analysis of organizations’ challenges and considerations in their digital transformation journeys.